A leitura literária em espaços não escolares e a universidade : diálogos possíveis para novas questões na formação de professores - Carvalho, Letícia Queiroz de (2012)
The research presents as its main point the teaching of literature in teacher development. It tells about the relationship between the University and nonschool spaces. It starts from the belief in the social aspects of literature and reading that not only sets in within the school environment, showing therefore our relations and social practices (BENJAMIN, 1996; FREIRE, 1987, 1996). We seek to answer questions like: is it possible to establish dialogues between literature at the University and the one that exists in non school spaces? What kind of Portuguese Language and Literature teacher we aim to form in graduation courses? What changes could be made during supervised periods in both Portuguese and Pedagogy courses from the insertion of literary reading in social projects that go beyond the school environment? To develop this research, it was chosen the qualitative research methodology, which focuses participant observation and intervention and also with some peculiarities of action research methodology. Our investigative actions occurred in literary workshops with graduation students of Literature and Pedagogy, in non formal education spaces - nursing homes, group homes, and other cultural centers - places that allowed us an outside movement (BAKHTIN, 2000, 2010) coming from the articulation of differences among these reading practices which showed provoking issues for a redefinition of teaching as a profession (NÓVOA, 1992, 2002, 2009; ZEICHNER, 1997, 2000, 2008). The results indicate the reformulation of supervised periods should be guided by discussions that should promote the integration of the literature teacher in any social space which allows any conscious and responsible movement while participating in culture.